Veranderings in die NG Kerk se sosio-politieke omgewing: Refleksie op Kerkordes 1962 en 1998 - Strauss, Pieter J. (HTS teologiese studies, 2023)
Socio-political changes in the Dutch Reformed Church: Reflected in church orders 1962 and 1998. The Confessio Belgica or Dutch Confession of Faith (1561), article 29 confesses 3 indications regarding the marks of a true church: the scriptural-based preaching of God’s Word, the scriptural service of the sacraments, and the maintaining of church discipline. A reformed church order gives guidelines how this should be achieved practically by the church. In applying itself to the entire life of a church, its church order normally reflects aspects of the present societal surroundings of this church. This is especially true of important socio-political changes of which the church, as part of society, and with its order made in that situation, normally gives indications. In being a visible church, every organised church gives reflections of some of its ties with the state authorities of the country and its politics. These reflections also communicate something of the approach of this church to these issues. The norm for the articles of a reformed church order should be the Word of God, but in guiding the church to fulfil its task, a church order also reflects aspects of the customs and culture in which it finds itself.Contribution: This article formulates the purpose of a church order and the fact that such an order carries reflections of the societal customs and values in the context of that church. From a church-historical and church-political perspective, a research study of the church orders of the Dutch Reformed Church of 1962 and 1998 is used to determine something of the stance of this church in the days of social unrest in the 1960s and social changes in South Africa in 1994.